High accuracy of proximity extension assay technology for the quantification of plasma brain natriuretic peptide. Issue 8 (23rd May 2018) - Arrigo, Mattia; Vodovar, Nicolas; Von Moos, Seraina; Masson, Elisabeth; Segerer, Stephan; Cippà, Pietro E.; Mebazaa, Alexandre
Abstract : Background: Novel multiplex assays allow the simultaneous identification of a large number of plasma proteins. While these new technologies have been shown to be highly sensitive and accurate for the identification of plasma proteins, the use of this technology to quantify those proteins has not been properly investigated. In this pilot study, we tested the accuracy of the proximity extension assay (PEA) for the quantification of the cardiac biomarker brain natriuretic peptide (BNP) compared to a standard clinically approved method. Methods: Concentrations of BNP were assessed in 120 plasma samples from 30 patients with PEA and compared to chemiluminescent microparticle immunoassay (CMIA). Venous blood samples were collected from in tubes containing ethylenediaminetetraacetic acid, centrifuged within 6 hours at 3, 500 rpm for 15 minutes at 4°C, frozen and stored at −80°C until analyzed. Correlation between the CMIA and PEA techniques was tested using the Spearman's rank correlation coefficient (rho) and the agreement was described with a Bland‐Altman plot. Results: Brain natriuretic peptide values obtained by CMIA and PEA were highly correlated (Spearman's rho = 0.865, P < .0001). In two patients, PEA consistently overestimated resp. underestimated BNP values compared to CMIA. After removal of those two patients, a very high correlation between the two techniques was shown (rho = 0.966, P < .0001). A high agreement between the two techniques over the whole range of tested concentrations was shown. Conclusion: This pilot study showed for the first time an excellent correlation between a clinically approved method and the PEA‐based approach for quantification of circulating plasma BNP.